Makan dalam Keterbatasan : Menggali Pemeliharaan Allah Refrleksi Iman Mahasiswa Teologi : 2 Raja-Raja 4 : 42-44 - Tabita Sarah Ningsih Samosir; Satriadi Tumangger (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2025)
The theme of God's provision in limitations is highly relevant to theology students, who often face various challenges in their academic and spiritual journeys. The story in 2 Kings 4:42-44, where the prophet Elisha distributes twenty barley loaves to a hundred people, provides a powerful illustration of how God can turn limitations into blessings. Theology students often feel inexperienced and limited in resources to serve the community, but Elisha's example teaches that intention and trust in God are far more important than the amount of resources one has. Limitations can also trigger a crisis of faith, especially when the demands of academics and daily life increase. Therefore, it is important for students to realize that limitations are not obstacles to God, but opportunities to experience His love and power. This paper aims to explore how God's provision in limitations can be the basis for learning faith that shapes the character and ministry of theology students. By understanding this concept, it is hoped that students can serve sincerely and trust in God in every aspect of their lives.